2014
DOI: 10.1620/tjem.232.223
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Student Tutors in Problem-Based Learning of Undergraduate Medical Education

Abstract: Problem-based learning (PBL) is a teaching and learning method designed to develop clinical reasoning skills. Tutor performance in PBL affects both the process and outcome of student learning. In this study, we investigated the factors that influence the evaluation by undergraduate students on the performance of tutors in medical education. From April 2009 to February 2010, 49 PBL sessions were conducted for 191 3rd-and 4th-year medical students at Saga Medical School in Japan. Twenty-nine 6th-year students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Every group received equivalent tutors, either from student tutor or faculty tutor. This study found that student gender, quality of case scenarios and tutor backgrounds were correlated with "excellent scores" in tutor performances [9]. This finding is in line with the previous researches by Dolmans, et.al.…”
Section: Results and Analysissupporting
confidence: 92%
“…Every group received equivalent tutors, either from student tutor or faculty tutor. This study found that student gender, quality of case scenarios and tutor backgrounds were correlated with "excellent scores" in tutor performances [9]. This finding is in line with the previous researches by Dolmans, et.al.…”
Section: Results and Analysissupporting
confidence: 92%
“…01). Similar findings were reported in a Japanese study where a rating of 'excellent' regarding case scenarios was associated with excellent tutor evaluations (OR of 12.43 [95% CI: 10.28-15.03) [14]. …”
Section: Discussionsupporting
confidence: 87%
“…PBL is defined as a student-centered pedagogy in which participants are allocated in groups of up to 8 persons under non-directive tutors and given tasks or challenges that reflect situations relevant to the working environments they will experience2. In this way, the learners are empowered to integrate theory and practice, and apply knowledge and skills to develop a viable solution to the problem34. PBL represents a paradigm shift from traditional pedagogy, which is more often lecture-based learning (LBL).…”
mentioning
confidence: 99%